SCREENING OF LACTIC ACID BACTERIA FROM SELECTED SAUDI HONEY PRODUCED BY APIS MELLIFERA JEMENTICA - Muhammad Barkaat Hussain; Yasser Mahmoud Kamel Mohamed Aly; Asif Ahmad M. Jiman-Fatani; Zia Ullah; Imtiaz Ahmad Qureshi; Marwan A Bakarman; Muhammad Yasir; Saleh M. Al-Maaqar (Journal of Animal and Plant Sciences, 2023)
Honey is receiving worldwide attention as an excellent source of probiotics because it contains lactic acid bacteria (LAB) derived from bees as well as multiple essential nutrients, including prebiotics, required for maintaining and enhancing the growth of probiotics. There is limited information on the presence of LAB in honey, especially in Saudi Arabia. Consequently, the purpose of the current study was to isolate and identify LAB from selected honey samples produced by Apis mellifera jementica obtained from various areas around Saudi Arabia using classical cultivation methods and 16S rDNA sequence analysis. The current study examined seventeen commercially sold honey samples, mainly from Saudi Arabia's Al-Baha, Aseer, and Jeddah (Hada Al-Sham) regions.LAB were isolated from honey samples and grown on De Man-Rogosa-Sharpe (MRS) agar. The phenotypic characterization of honey isolates was ascertained using Gram staining, microscopy, and the catalase test. Using 16S ribosomal RNA gene sequencing, isolates were genotypically described. Lactobacillusrhamnosus and Enterococcusfaecium were identified from Sidr, Talah, and Somra honey produced by Apis mellifera jementica. The P02, P14, and Con-6 strains were found to share > 99% of their DNA with Lactobacillus rhamnosus by 16S rRNA sequencing investigations, while the P01, P03, and P04 strains shared > 99% of their DNA with Enterococcus faecium. Additionally, the phylogenetic tree reveals that the honey strains isolated from Sidr (P02) and Talah (P14) were closely linked to Lactobacillus rhamnosus, whereas P01 (Sidr), P03 (Somra), and P04 (Somra) were most closely connected to Enterococcus faecium.According to the research, honey produced by Apis mellifera jementica is a beneficial source of probiotics and lactic acid bacteria.
Keywords: probiotics; lactic acid bacteria; honey; Sidr; Lactobacillus rhamnosus; prebiotics; Enterococcus faecium